2020
DOI: 10.1136/rmdopen-2019-001161
|View full text |Cite
|
Sign up to set email alerts
|

The impact of certolizumab pegol treatment on the incidence of anterior uveitis flares in patients with axial spondyloarthritis: 48-week interim results from C-VIEW

Abstract: BackgroundAcute anterior uveitis (AAU) is the most common extra-articular manifestation in patients with axial spondyloarthritis (axSpA). C-VIEW investigates the impact of the Fc-free TNF inhibitor certolizumab pegol (CZP) on AAU flares in patients with active axSpA at high risk of recurrent AAU.MethodsC-VIEW (NCT03020992) is a 96-week ongoing, multicentre, open-label, phase 4 study. Included patients had an axSpA diagnosis, a history of recurrent AAU (≥2 AAU flares, ≥1 flare in the year prior to study entry),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 37 publications
3
31
0
Order By: Relevance
“…Relevant improvements in patients' axSpA disease activity, according to ASDAS, BASDAI and ASAS responses, were also demonstrated in the C-VIEW study, which were in line with previous studies of CZP. 24,25,27 Moreover, CZP was well tolerated during the 96-week treatment period; no new safety signal was identified compared to previous reports 28 and only five of 89 subjects who initiated CZP discontinued the study due to adverse events, which was consistent with previous reports of CZP in axSpA. 24,25 The incidence and type of adverse events were also consistent with the known safety profile of CZP.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Relevant improvements in patients' axSpA disease activity, according to ASDAS, BASDAI and ASAS responses, were also demonstrated in the C-VIEW study, which were in line with previous studies of CZP. 24,25,27 Moreover, CZP was well tolerated during the 96-week treatment period; no new safety signal was identified compared to previous reports 28 and only five of 89 subjects who initiated CZP discontinued the study due to adverse events, which was consistent with previous reports of CZP in axSpA. 24,25 The incidence and type of adverse events were also consistent with the known safety profile of CZP.…”
Section: Discussionsupporting
confidence: 86%
“…Further information on details recorded by treating ophthalmologists for AAU flares, both during the 2-year period prior to baseline and during the treatment period, have previously been reported. 28 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data from the Swedish biologics registry and from a US claims database reported that adalimumab and infliximab are associated with reduced risk of acute anterior uveitis development and flares in patients with AS, compared with etanercept [ 58 , 59 ]. Data for golimumab and certolizumab are also suggestive of efficacy for uveitis in axSpA [ 60 , 61 ]. There are currently very limited data available for IL-17A and JAK inhibitors in uveitis, with secukinumab failing to meet the primary efficacy endpoints in three small linked RCTs of non-infectious uveitis [ 62 ].…”
Section: Biologic Dmards In Axspamentioning
confidence: 99%